If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 29 = -1x + 15 Reorder the terms: 29 + -2x = -1x + 15 Reorder the terms: 29 + -2x = 15 + -1x Solving 29 + -2x = 15 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 29 + -2x + x = 15 + -1x + x Combine like terms: -2x + x = -1x 29 + -1x = 15 + -1x + x Combine like terms: -1x + x = 0 29 + -1x = 15 + 0 29 + -1x = 15 Add '-29' to each side of the equation. 29 + -29 + -1x = 15 + -29 Combine like terms: 29 + -29 = 0 0 + -1x = 15 + -29 -1x = 15 + -29 Combine like terms: 15 + -29 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14
| -6x-2y=-4 | | 2+2f=8 | | 4(x-1)=2(3y-1) | | 200m-100m+57900=60300-200m | | .23+480.48=x | | M-3n+5= | | 9p^2(p+1)=4(p+1)-9(p+1) | | 4y+11=79 | | 4.75m+15=3m+24+m-4 | | 203.75/(-0.1)= | | .5n=3n-20 | | 5(x+9)-4=5 | | y7+6=11 | | 2x+4=2x+4.000000000000000000000000000000000000000000000000000000001 | | 4y-7=39 | | 0.5n-5=3n-25 | | 2x-5=39(7+2x) | | 2sin(x)-4-cos(x)=0 | | 6u-6=-9(u-1) | | ifBC=RLthen | | 36+12m^2+m^4=0 | | 4a*3a= | | ln(6x+2)=ln(3x-19) | | -4.3-3z-2.9-z=-3z+5.7 | | -8m-8n+p-2=-10n-9p+8 | | 12*x^2-4=0 | | t(2t+-1)=1 | | 10-(4x-1)=8-5x | | 7x+21(2x-3)=180 | | 8c*3c= | | 3x+22x-4=5(5x+6) | | (-7b+4a)+(-6a-9b)= |